Evolution of Hox gene clusters in deuterostomes - Pascual-Anaya, Juan; D'Aniello, Salvatore; Kuratani, Shigeru; Garcia-Fernàndez, Jordi (BMC, 2013)
Hox genes, with their similar roles in animals as evolutionarily distant as humans and flies, have fascinated biologists since their discovery nearly 30 years ago. During the last two decades, reports on Hox genes from a still growing number of eumetazoan species have increased our knowledge on the Hox gene contents of a wide range of animal groups. In this review, we summarize the current Hox inventory among deuterostomes, not only in the well-known teleosts and tetrapods, but also in the earlier vertebrate and invertebrate groups. We draw an updated picture of the ancestral repertoires of the different lineages, a sort of “genome Hox bar-code” for most clades. This scenario allows us to infer differential gene or cluster losses and gains that occurred during deuterostome evolution, which might be causally linked to the morphological changes that led to these widely diverse animal taxa. Finally, we focus on the challenging family of posterior Hox genes, which probably originated through independent tandem duplication events at the origin of each of the ambulacrarian, cephalochordate and vertebrate/urochordate lineages.
Keywords: Genética evolutiva; Embriología; Hox clusters; Hox evolution; Deuterostomes; Evolution